What are the care needs of families experiencing cardiac arrest?: A survivor and family led scoping review. (November 2021) - Douma, Matthew J.; Graham, Timothy A.D.; Ali, Samina; Dainty, Katie N.; Bone, Allison; Smith, Katherine E.; Dennet, Liz; Brindley, Peter G.; Kroll, Thilo; Frazer, Kate
Abstract: Aim: The sudden and unexpected cardiac arrest of a family member can be a grief-filled and life-altering event. Every year many hundreds of thousands of families experience the cardiac arrest of a family member. However, care of the family during the cardiac arrest and afteris poorly understood and incompletely described. This review has been performed with persons with lived experience of cardiac arrest to describe, "What are the needs of families experiencing cardiac arrest?" from the moment of collapse until the outcome is known. Methods: This review was guided by specific methodological framework and reporting items (PRISMA-ScR) as well as best practices in patient and public involvement in research and reporting (GRIPP2). A search strategy was developed for eight online databases and a grey literature review. Two reviewers independently assessed all articles for inclusion and extracted relevant study information. Results: We included 47 articles examining the experience and care needs of families experiencing cardiac arrest of a family member. Forty one articles were analysed as six represented duplicate data. Ten family care need themes were identified across five domains. The domains and themes transcended cardiac arrest setting, aetiology, family-member age and family composition. The five domains were i) focus on the family member in cardiac arrest, ii) collaboration of the resuscitation team and family, iii) consideration of family context, iv) family post-resuscitation needs, and v) dedicated policies and procedures. We propose a conceptual model of family centred cardiac arrest. Conclusion: Our review provides a comprehensive mapping and description of the experience of families and their care needs during the cardiac arrest of a family-member. Furthermore, our review was conducted with co-investigators and collaborators with lived experience of cardiac arrest (survivors and family members of survivors and non-survivors alike). The conceptual framework of family centred cardiac arrest care presented may aid resuscitation scientists and providers in adopting greater family centeredness to their work.